Mengurai Paradoks Green Brand Image–Green Perceived Quality: Peran Mediasi Green Trust pada Konsumen Natur-E di Indonesia - Vitratin, Vitratin; Zahra, Fahmiati; Yuniastuti, Rina Milyati; Ismulyani, Heditia Umi; Inonu, Saddam Hussein (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2025)
Rising environmental awareness encourages green cosmetic companies to build a green brand image. However, perceived good quality is not always followed by a good green image, which causes a paradox in green marketing strategies, especially in emerging markets. The purpose of this study was to examine green brand image against perceived good green quality and green trust as a mediating variable among Natur-E supplement customers in Bandar Lampung. This study conducted a quantitative survey of 198 Natur-E customers aged at least 18 years who were purposively selected. Structural Equation Modeling–Partial Least Squares (SEM-PLS) was used to analyze the data. The results showed that green brand image had a negative and significant effect on perceived green quality, but a positive and significant effect on green trust. Green trust also had a positive and significant effect on perceived green quality, and partially mediated the relationship between green brand and green quality with a mediating effect of 61.9%. The results indicate that green image does not automatically improve perceived quality without supporting customer trust. Natur-E should align green claims with product quality and increase trust through consistent sustainability practices. Theoretically, this study adds to the green marketing literature by revealing the paradox between green brand image and perceived quality, and emphasizing that green beliefs play a mediating role in the context of green cosmetics in emerging markets..